2017
DOI: 10.21451/1984-3143-ar0005
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the buffalo species for andrological evaluation results of four years of study and weekly semen collection schedule

Abstract: The aim of the present review is to provide complementary information about reproductive characteristics of male buffaloes having as perspective a four -year-study based on a weekly seminal collection schedule and collection of data in partner properties of several regions of Brazil. Aspects of testicular growth, reproductive behavior and characteristics of 1477 ejaculates of 13 donors are discussed in conjunction with data available in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
(14 reference statements)
1
10
0
1
Order By: Relevance
“…The minimum and maximum ejaculate volumes of buffalo bulls observed in the study were 0.6 and 9.0 ml, respectively. Several reports have shown that semen ejaculate volume of Murrah buffalo bulls ranged between 2.78 and 5.0 ml (Bhakat, Mohanty, Raina, Gupta, & Khan, 2011; Bhakat et al., 2015; Henry et al., 2017). In this study, aggressiveness, penile erection and reaction time were not correlated with semen volume.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum and maximum ejaculate volumes of buffalo bulls observed in the study were 0.6 and 9.0 ml, respectively. Several reports have shown that semen ejaculate volume of Murrah buffalo bulls ranged between 2.78 and 5.0 ml (Bhakat, Mohanty, Raina, Gupta, & Khan, 2011; Bhakat et al., 2015; Henry et al., 2017). In this study, aggressiveness, penile erection and reaction time were not correlated with semen volume.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, nas condições brasileiras, a variação da circunferência escrotal pode ser de 24,5 cm a 34 cm em animais até 60 meses. Este fato nos remete que não há a padronização dos touros bubalinos e, que a seleção para melhoramento genético através do exame andrológico pode estar um pouco atrasada nas condições nacionais, quando comparada com os bovinos [8].…”
Section: Discussionunclassified
“…After "Flehmen behavior" is confirmed the receptivity, exposure of the penis may occur, and the ejaculatory impulse is less intense than in bovine bulls. The buffalo's normal ejaculate is milky-white to yellowish and the appearance looks watery to creamy, depending on the concentration of spermatozoa, rarely exceeding 5 ml (Henry et al, 2017). Male buffalo are more sensitive to thermal stress than females due to their low heat regulation mechanism (Hameed et al, 2016a).…”
Section: Male Buffalomentioning
confidence: 99%
“…After this period, the genital system reaches its production of hormones and spermatozoa, producing an ejaculate with characteristics acceptable for freezing, this phase is called sexual maturation, which is achieved around 22 and 24 months of age, in a study with 456 male animals at this age with a minimum weight of 137.5 kg and a maximum weight of 540 kg of body weight. By analyzing the andrological evaluation in buffaloes, scrotal circumference (SC) has a fundamental value in the clinical-andrological exam, since it has a positive correlation with body weight and thoracic perimeter, and it is possible to predict the animal's reproductive capacity and its sperm production and their progeny (relation to sexual precocity) (Henry et al, 2017).…”
Section: Male Buffalomentioning
confidence: 99%
See 1 more Smart Citation